The nutritional status and feeding practices of sheep grazing cultivated pasture and crop residues in a mediterranean environment - Brand, Tertius Swanepoel (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhDAgric)--Stellenbosch University, 1996.